2017
DOI: 10.1049/iet-cdt.2016.0149
|View full text |Cite
|
Sign up to set email alerts
|

Temperature gradient‐aware thermal simulator for three‐dimensional integrated circuits

Abstract: Nowadays, thermal simulators of integrated circuits (ICs) at architectural level tend to neglect thermal effects in temperature-dependent factors (such as leakage power and thermal conductivity) and a heat dissipation mechanism for thermal radiation at the early stages of IC design. Hence, the analysis results of thermal simulators may be not sufficient to reflect the physical-thermal interactive effects of ICs. This study presents a temperature gradient-aware thermal simulator for threedimensional ICs (called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The thermal circuit represents the temperature of the device. 30) We adopt the Cauer-type formation of the thermal circuit, in which each element represents the thermal property of the corresponding layers. The current sources, P0, P1, P2, P3, and P4 represent the heat generation of each layer, described as follows:…”
Section: Thermal Circuitmentioning
confidence: 99%
“…The thermal circuit represents the temperature of the device. 30) We adopt the Cauer-type formation of the thermal circuit, in which each element represents the thermal property of the corresponding layers. The current sources, P0, P1, P2, P3, and P4 represent the heat generation of each layer, described as follows:…”
Section: Thermal Circuitmentioning
confidence: 99%
“…In [23], Pi, et al proposed a fast and implementable full chip-scale numerical simulation method for thermal management of 3D-IC by using the compact thermal resistance network and found that the proposed method could improve the simulation accuracy (temperature difference < 7.5%) and considerable computational cost reduction (grid number reduced by > 77%). Lu, et al presented a temperature gradient-aware thermal simulator for three-dimensional ICs (called 3D-TarGA) at the architectural level in [24]. In [25], Xiao, et al proposed a fast and accurate equivalent approach based on finite element analysis (FEA) for estimating the equivalent thermal conductivity of 3D IC device, and the approach was validated by 3D FEA method.…”
Section: Introductionmentioning
confidence: 99%
“…The scaling in high‐performance microprocessor systems, which integrate more transistors into a single chip, leads to higher power density and temperature and may cause a localised high‐temperature region usually known as thermal hotspot . Thermal hotspots have adversarial effects on performance, reliability, cooling costs and lifespan [5]. According to [6], a change of operating temperature by 1015°normalC results in a 2 x reduction in lifespan of a device.…”
Section: Introductionmentioning
confidence: 99%